186 ACUTE GASTRIC OUTLET OBSTRUCTION AND SUBSEQUENT GASTRIC PERFORATION IN AN INFANT ON PROSTAGLANDIN INFUSION FOR HYPOPLASTIC LEFT HEART SYNDROME. (1st January 2005) - Vargas, A.; Barkemeyer, B. M.; Minkes, R. R.; Mulder, T. J.; Newman, W.
Abstract : Background: Prostaglandins are frequently used to maintain patency of the ductus arteriosus in lethal ductal-dependent cyanotic congenital heart disease. Prostaglandin-induced gastric outlet obstruction resulting from antral hyperplasia is a known complication that has been associated with prolonged exposure to prostaglandin (> 120 hours) and a high total cumulative dose (> 1560 μg/kg). There are no case reports in the literature of gastric perforation in these patients. Case Report: We present a 3.5 kg female infant born at 41 weeks of gestation with a prenatal diagnosis of hypoplastic left heart by fetal echocardiography. She was placed on prostaglandin infusion (0.05 μg/kg/min) shortly after birth. Her clinical course was uncomplicated until she developed abdominal distention on the 3rd day of life. Plain abdominal films demonstrated a large dilated stomach bubble with no air in the small intestine through the rectal vault. Despite gastric decompression via nasogastric tube, a follow-up abdominal film on the 4th day of life showed a large amount of free air in the peritoneum. At the time of surgery, the infant was found to have a large rupture of the stomach extending from near the gastroesophageal sphincter along the greater curvature to the antrum with a large amount of devitalized tissue. There was no evidence of mechanical obstruction through the pylorus. After gastric repair, the infant stayed in the neonatal intensive care unit until the 28th day of life, when a Norwood procedure was performed. At the time of hospital discharge (60th day of life), she was tolerating continuous feeds through a jejunostomy tube. Discussion: The initial clinical and radiographic signs of gastric outlet obstruction were seen after our patient had received < 72 hours of prostaglandin infusion with a total cumulative dose of < 216 μg/kg. The occurrence of this complication in a shorter period of time and at a much lower cumulative dose than previously reported emphasizes the need for increased awareness of this problem in order to avoid additional morbidity, for example gastric perforation.